Microbial food webs share similar biogeographic patterns and driving mechanisms with depths in oligotrophic tropical western Pacific Ocean - Shao, Qianwen; Sun, Dong; Fang, Chen; Feng, Yunzhi; Wang, Chunsheng (Frontiers in Microbiology, 2023)
Microbial food web (MFW) dominates the energy flow in oligotrophic tropical open ocean pelagic ecosystems. Understanding biogeographic patterns and driving mechanisms of key components of the MFW is one of the central topics in current marine ecology, and such knowledge is also essential for planning of marine protected areas. Investigations were conducted along an 1100-km horizontal gradient and in the full-water column vertical gradient of the oligotrophic tropical western Pacific Ocean. High-throughput sequencing and association networking methods were used to analyze the community structure and interspecies interactions of MFW. The structure of MFW significantly differed with depths, but not across horizontal gradients. Bacteria and microeukaryotes were interconnected and had more predominantly positive and negative linkages in the aphotic layers. Key components of MFW exhibited similar biogeographic patterns and driving mechanisms. Geographic distance exerted minimal effects on the distribution patterns of the microbial food web, while environmental factors played more important roles, especially for temperature and inorganic nutrients. Stochastic processes were more important in the microbial food webs of the 5–200 m layer than the > 500 m layer, and drift explained the majority of stochastic processes. Moreover, only a weak but not significant driving force for North Equatorial Current on the east-west connectivity of the microbial food web was found in the upper layers. This knowledge is a critical fundamental data for future planning of marine protected areas targeting the protection of tuna fishing in the western Pacific Ocean.